2016
DOI: 10.1038/cddis.2016.398
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 deficiency ameliorates Graves’ disease severity by suppressing thyroid epithelial cell hyperplasia

Abstract: Signal transducer and activator of transcription 6 (STAT6) is involved in epithelial cell growth. However, little is known regarding the STAT6 phosphorylation status in Graves' disease (GD) and its role in thyroid epithelial cells (TECs). In this study, we found that STAT6 phosphorylation (p-STAT6) was significantly increased in TECs from both GD patients and experimental autoimmune Graves' disease mice and that STAT6 deficiency ameliorated GD symptoms. Autocrine IL-4 signalling in TECs activated the phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Our recent observations has verified the IL-4 expression in the thyroid was significantly increased while serum IL-4 level were unaffected in EAGD mice. IL-4 derived from thyroid epithelial cells (TEC) may contribute to the pathogenesis of GD by stimulating unrestrained TEC hyperplasia [13]. Cytokines from thyroid tissue perhaps play a more critical role in the pathogenesis of GD than circulating serum cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent observations has verified the IL-4 expression in the thyroid was significantly increased while serum IL-4 level were unaffected in EAGD mice. IL-4 derived from thyroid epithelial cells (TEC) may contribute to the pathogenesis of GD by stimulating unrestrained TEC hyperplasia [13]. Cytokines from thyroid tissue perhaps play a more critical role in the pathogenesis of GD than circulating serum cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In our very recent studies, we found IL-4 was infiltrated in the thyroid tissue of experimental autoimmune Graves' disease (EAGD) mice. IL-4 acted in an autocrine manner to activate p-STAT6 signal and stimulate unrestricted cell growth, thus aggravating GD [13]. Wang et al found direct injection of TNF-α into the thyroids of mTg-primed mice can induce thyrocyte apoptosis, indicating that pro-inflammatory TNF-α may play a critical role in thyroid destruction [14].…”
Section: Thyroid Function Test and Antithyroid Antibodiesmentioning
confidence: 99%
“…Color formation was discontinued, and the intensity of the color was measured at OD 450 nm on an ELISA reader. The results of individual samples were obtained after the negative control was assigned to a value of 0.1 μg/L, and a standard curve was created 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Signal Transducer and Activator of Transcription 6 (STAT6), the downstream signaling pathway of IL-4 and IL-13, is a key cytokine of macrophage differentiating toward M2 phenotype. [24,25] For instance, Xiao et al reported an M2 TAMs-targeted nanodrug incorporating AS and anti-IKK𝛽 siRNA. The nanodrug reversed the TME with increased CD8 + T cells and reduced Tregs via switching the polarization of M2-TAMs toward the M1 phenotype for enhanced tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%